Laryngeal lymphangioma: a case report - Çağlar Çallı; Ercan Pınar; Semih Öncel; Demet Etit (Turkish Archives of Otorhinolaryngology, 2008)

(untitled)
Lymphangiomas are uncommon benign congenital lymphatic tumors of childhood. They are found in all parts of the body structure but rarely occur in the larynx. The presence of laryngeal lymphangiomas was rarely reported in the literature. A 23- year-old male presented with progressive difficulty in swallowing for a year and occasional hoarseness. Indirect laryngoscopy revealed a tumoral mass in 3x3 cm size with a vascularized appearance which originated from left endolaryngeal side of epiglottis. The patient underwent left lateral pharyngotomy under general anesthesia. The perioperative frozen section was reported as favored benign lymphangioma. Postoperative histopathologic examination revealed lymphangioma.